2023
DOI: 10.31235/osf.io/qzmf6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The potential of inclusive and collaborative Open Research processes at the science-policy interface

Abstract: Proponents of Open Research often assert that it can support evidence-based policy-making by making scientific outputs more readily available to policy-makers and other policy actors, yet there is little empirical work to support or deny this claim. This paper fills this void by reporting the results of a qualitative study with researchers who regularly work at the science-policy interface. We found that there is little evidence that Open Research products, namely Open Access and open data, which aim at increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We refer to such an approach as ‘global thinking’, a term that has two distinct senses [ 95 ]. Firstly, thinking should be ‘global’ in that approaches should be joined-up to target reform of the research ecosystem as a whole rather than taking atomistic policy actions that target specific aspects of Open Research while leaving others unaddressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to such an approach as ‘global thinking’, a term that has two distinct senses [ 95 ]. Firstly, thinking should be ‘global’ in that approaches should be joined-up to target reform of the research ecosystem as a whole rather than taking atomistic policy actions that target specific aspects of Open Research while leaving others unaddressed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, research has shown that women [ 45 ], scholars within the social sciences and humanities [ 46 ], those from middle- and lower-income nations [ 47 , 48 ] and early career researchers [ 49 ] experience disadvantage relative to others when it comes to OA publishing. Since support for APCs is typically available from funders or research institutions, actors beyond the academy, such as civil society organizations or industry, are also excluded from OA publishing [ 50 , 51 ]. Additionally, those from the periphery are more at risk of exploitation by low-quality, predatory journals that have colonized OA publishing in certain geographies, which leads to their contributions being dismissed and overlooked [ 52 , 53 ].…”
Section: Barriers To the Equitable Implementation Of Open Researchmentioning
confidence: 99%
“…There is a long research experience of conducting surveys in order to understand the knowledge exchange practices in relation to a variety of collaborative practices (Díaz-Faes et al, 2023), modes of knowledge exchange with industry (D'Este & Patel, 2007), exchange with policy (Thune et al, 2023), innovation practices in industry through the Oslo Manual (Bloch, 2007;Gault, 2020;OECD & Eurostat, 2018), innovation in the public sector (Arundel et al, 2019), and practices of Responsible Research and Innovation (RRI) (Holtrop et al, 2022). Some studies aimed at monitoring OS processes also relied on surveys: for example on sharing of research materials (Shibayama et al, 2012), open peer review (Ross-Hellauer et al, 2017), policy use (Cole et al, 2023), engagement with non-academics (Lawson et al, 2019), integrity (Schneider et al, 2023), or broader perceptions and habits of OS (Ollé et al, 2023). To our knowledge, conducted the only survey looking into the multiple dimensions of OS, showing differences by field and region.…”
Section: The Need To Gather New Data Sources and Surveysmentioning
confidence: 99%